Theoretical study of magnetic and magnetocaloric properties and MCE modeling by the mean-field theory in CoFeCuO4 spinel ferrite - Nasri, M. (2022)
In this research paper, we are basically interested in the theoretical investigation of magnetic and magnetocaloric properties of CoFeCuO4 spinel ferrite. Our sample was prepared using the sol-gel method. The XRD analysis confirmed the cubic spinel structure with the Fd (3) over barm space group exhibited by our compound. Furthermore, the positive slope detected in the Arrott plots is indicative of the second-order phase transition. Based on the phenomenological model of Hamad, the simulation of the magnetization M (T) goes in good agreement with the experimental results. Moreover, the magnetic entropy change (-Delta S-M) estimations by Hamad's model and Landau theory go in good accordance with the experimental results determined using Maxwell relations above the Curie-temperature T-C, and they show a divergence below this temperature. The relative cooling power (RCP) has a value of 64.342 J.kg(-1) under a magnetic field of 5T, which is suggestive that our compound can be a promising material for the magnetic refrigeration (MR) application. Finally, the validity of the mean-field theory to the theoretical study was proven through the compatibility inferred between the (-Delta S-M(max)) and RCP values obtained by the Maxwell relation and the Bean-Rodbell model.